2018
DOI: 10.1016/j.jcpa.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Dental and Temporomandibular Joint Pathology of the Grey Wolf ( Canis lupus )

Abstract: Skulls from 392 grey wolves (Canis lupus) were examined macroscopically according to predefined criteria. Two hundred and seven skulls were included in this study, comprised of 124 young adults (59.9%) and 83 adults (40.1%); of these, 65 (31.4%) specimens were from male wolves and 104 (50.3%) were from females, with 38 (18.4%) of unknown sex. Out of 8,694 possible teeth, 8,339 (95.9%) were present for evaluation. Fifty-five teeth (15.5%) were absent congenitally, 30 (8.5%) were lost during life and 270 (76.1%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
(23 reference statements)
2
10
0
Order By: Relevance
“…Szuma (1999) similarly found that just 2.5% of 1453 red fox skulls had enamel hypoplasia, while Evenhuis et al (2018) identified only a single case among 637 grey fox skulls. Results were similar in a study of wolves, with 2.4% of skulls showing signs of enamel hypoplasia (Döring et al 2018). In a separate study, only 17 dogs and wolves were affected out of 544 individuals examined by Losey et al (2014).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Szuma (1999) similarly found that just 2.5% of 1453 red fox skulls had enamel hypoplasia, while Evenhuis et al (2018) identified only a single case among 637 grey fox skulls. Results were similar in a study of wolves, with 2.4% of skulls showing signs of enamel hypoplasia (Döring et al 2018). In a separate study, only 17 dogs and wolves were affected out of 544 individuals examined by Losey et al (2014).…”
Section: Discussionsupporting
confidence: 71%
“…Second stage periodontal disease is typically reported in previous research and, therefore, shows higher prevalence than in the current study. Döring et al (2018) An additional goal of the current research was to evaluate skull and mandible pathologies. Temporomandibular joint changes and osteoarthritis were excluded from the study, though a fuller analysis of these issues is warranted.…”
Section: Discussionmentioning
confidence: 99%
“… Valkenburgh (1988) refers that the most fractured teeth in African carnivores that consume bones, such as hyenas, are the canine teeth, followed by the premolars, first molars and incisive teeth. In Alaskan wolves, canines and premolars were found with fractures teeth in around half of the collection ( Döring et al., 2018 ), in opposition to the data published by Losey, Jessup, Nomokonova, and Sablin (2014) who noted fractures in 27.8% of wolves teeth, mainly in maxillary incisors and canines. The same team refer that male wolves suffered more tooth fracture than females, being the Subarctic Russian wolves those having more females than males affected.…”
Section: Discussionmentioning
confidence: 64%
“…However, natural history collections through their specimens and associated documentation, are important source of information allowing, for example, for collecting medical data from both domestic and wild animals. In fact, several species were already assessed for dental abnormalities using museum collection, as the case of gray wolf ( Canis lupus ) ( Barber-Meyer, 2012 ; Döring, Arzi, Winer, Kass, and Verstraete, 2018 ; Janssens, Verhaert, Berkowic, and Adriaens, 2016 ; Pavlović, Gomerčić, Gužvica, Kusak, and Huber, 2007 ; Valkenburgh, 1988 ; Vilà, Urios, and Castroviejo, 2008 ), red fox ( Vulpes vulpes ) ( Szuma, 2014 ), African lion ( Panthera leo ), leopard ( P. pardus ), jaguar ( P. onca ), cheetah ( Acinonyx jubatus ), puma ( Puma concolor ), spotted hyena ( Crocuta crocuta ), striped hyena ( Hyaena hyaena ), and the African wild dog ( Lycaon pictus ) ( Valkenburgh, 1988 ), Southern sea otter ( Enhydra lutris nereis ) ( Winer, Liong, and Verstraete, 2013 ), Iberian lynx ( Lynx pardinus ) ( Collados, Garcia, and Rice, 2018 ), domestic dog ( Canis lupus familiaris ) ( MacKinnon, 2010 ), domestic cat ( Felis silvestris catus ) and free-living Soay sheep ( Ovis aries ) ( Arthur et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specimens were evaluated systematically for abnormalities using previously determined criteria (Table 1). This method has proven to be efficient and effective at consistently detecting signs of dental pathology and other osteological abnormalities such as temporomandibular osteoarthritis in other mammalian carnivores (Aalderink et al, 2015;Aghashani et al, 2016;Clark et al, 2017;Doring et al, 2018;Evenhuis et al, 2018). Presence of teeth was recorded and any missing teeth were categorized as artefactual loss, congenital absence or acquired loss.…”
Section: Methodsmentioning
confidence: 99%